2005
DOI: 10.1213/01.ane.0000159161.31276.db
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Injection Time and Light Smoking Decrease the Incidence of Fentanyl-Induced Cough

Abstract: We designed this study to evaluate the effect of injection time and smoking on fentanyl-induced cough. Four-hundred-fifty ASA class I-II patients, aged 18-80 yr and weighing 40-90 kg, scheduled for elective surgery were included. All patients received fentanyl (100 microg for patients weighing 40-69 kg and 150 microg for patients weighing 70-90 kg for clinical convenience) via the proximal port of a peripheral IV line on the forearm. Patients were randomly assigned to 3 groups of 150 patients each. Patients in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
93
7
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(105 citation statements)
references
References 18 publications
3
93
7
2
Order By: Relevance
“…I remain perplexed that researchers see so much of this problem, and wondered whether it was simply that they were using a higher dose of fentanyl compared to mine, but several of the papers these groups cite [5][6][7][8] used no more than 2 lg.kg )1 and still reported similar incidences.…”
mentioning
confidence: 99%
“…I remain perplexed that researchers see so much of this problem, and wondered whether it was simply that they were using a higher dose of fentanyl compared to mine, but several of the papers these groups cite [5][6][7][8] used no more than 2 lg.kg )1 and still reported similar incidences.…”
mentioning
confidence: 99%
“…Our study has shown that undiluted fentanyl, when administered through a peripheral venous line, provokes coughing in up to 32% of patients. Previous studies [1][2][3][4][5][6][7] have shown that the incidence of fentanyl-induced cough varies between 18% and 65%. In the study by Lin et al [1], 65% of the patients coughed following 2.5 lg.kg )1 fentanyl through a peripheral venous line within 2 s. A 46% incidence of cough has been reported with 7 lg.kg )1 fentanyl administered through a central venous catheter administered over 1 s by Bohrer et al [2].…”
Section: Discussionmentioning
confidence: 99%
“…From the pharmacokinetic point of view, the duration of drug injection may affect the peak plasma concentration, with a longer injection time resulting in a smaller peak concentration. Lin et al [7] suggested that slowing the rate of injection reduced not only the incidence but also the severity of coughing. Schlimp et al [14] also proposed that the slow intravenous administration of fentanyl could prevent fentanyl-induced coughing and therefore clinicians should try to prolong the administration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations